2019
DOI: 10.1093/bib/bbz057
|View full text |Cite
|
Sign up to set email alerts
|

iCircDA-MF: identification of circRNA-disease associations based on matrix factorization

Abstract: Circular RNAs (circRNAs) are a group of novel discovered non-coding RNAs with closed-loop structure, which play critical roles in various biological processes. Identifying associations between circRNAs and diseases is critical for exploring the complex disease mechanism and facilitating disease-targeted therapy. Although several computational predictors have been proposed, their performance is still limited. In this study, a novel computational method called iCircDA-MF is proposed. Because the circRNA-disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 67 publications
0
44
0
2
Order By: Relevance
“…Nonnegative matrix factorization (NMF) is a significant algorithm which can be applied in recommender system for data representation [32]. Recent years, NMF has been successfully utilized to predict potential interactions of drug-drug [41], lncRNA-protein [42], miRNA-disease [43], Microbe-disease [44], drug-disease [45], CircRNA-disease [46], etc.. NMF aims to obtain lncRNA-miRNA interaction score matrix by decomposing the original adjacency matrix into two low-dimensional nonnegative matrices directly [38]. In this work, the lncRNA-miRNA interaction adjacency matrix Y ∈ R 468×262 is decomposed into U ∈ R k×468 and V ∈ R k×262 , k is the sub-space dimensionality (k < rn/(r + n)).…”
Section: B Related Work 1) the Standard Nonnegative Matrix Factorizamentioning
confidence: 99%
“…Nonnegative matrix factorization (NMF) is a significant algorithm which can be applied in recommender system for data representation [32]. Recent years, NMF has been successfully utilized to predict potential interactions of drug-drug [41], lncRNA-protein [42], miRNA-disease [43], Microbe-disease [44], drug-disease [45], CircRNA-disease [46], etc.. NMF aims to obtain lncRNA-miRNA interaction score matrix by decomposing the original adjacency matrix into two low-dimensional nonnegative matrices directly [38]. In this work, the lncRNA-miRNA interaction adjacency matrix Y ∈ R 468×262 is decomposed into U ∈ R k×468 and V ∈ R k×262 , k is the sub-space dimensionality (k < rn/(r + n)).…”
Section: B Related Work 1) the Standard Nonnegative Matrix Factorizamentioning
confidence: 99%
“…They are mainly located in the cytoplasm or stored in exosomes, are unaffected by RNA exonucleases, are more stably expressed and less susceptible to degradation, and have been shown to exist in a wide variety of eukaryotic organisms Pradeep et al, 2020). The widespread existence of circRNAs suggests that they have certain biological functions as lncRNAs and microRNAs (miRNAs) play (Jiang et al, 2009(Jiang et al, , 2014(Jiang et al, , 2015Wang et al, 2014;Cheng L. et al, 2019;Liang et al, 2019;Wei and Liu, 2020;Yang et al, 2020). In recent years, studies have shown a diversity of formation mechanisms and biological functions of circRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs), non-coding RNA molecules with closed loop structures, play important roles in diverse human diseases, including cancers (Liu, Li, Luo, & Zhu, 2019;Wei & Liu, 2019). For instance, circDDX17 acts as a tumor suppressor by suppressing proliferation and accelerating apoptosis in colorectal cancer cells (Xiao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%